Hematemesis on Hepatic Cirrhosis Patients in Area with Limited Facilities - Yudha Klahan; Firas Farisi Alkaff (Biomolecular and Health Science Journal, 2018)
Esophageal variceal haemorrhage is one of the more dangerous complications of hepatic cirrhosis. Initial treatment can determine patient mortality and morbidity. But not all hospitals have adequate facilities and medicines to handle it. The 53-year-old woman came with a diagnosis of ascites and hematemesis. At the initial examination found hypotension. Laboratory results show anemia, thrombocytopenia, and leukocytosis. The next morning the patient's condition worsened and was transferred to ICU. During the ICU patients receive 10 lpm oxygen support, cefobactam, pantoprazole, PRC transfusion, and dopamine. Patients begin conscious  on the 5th day of treatment. Then the patient started getting diuretics on day 6 and propranolol on day 9. On day 13 the patient's condition improved and the patient was discharged for outpatient treatment. Limitations of the endoscopic tool cause not every hospital in Indonesia can perform emergency endoscopy for therapy. However, with rapid and appropriate pharmacological therapy, patients can be helped not to fall into mortality and prevent recurrent bleeding.